Association between latent toxoplasmosis and fertility parameters of men - Hlaváčová, Jana; Flegr, Jaroslav; Řežábek, Karel; Calda, Pavel; Kaňková, Šárka (Andrology, 2021)
BACKGROUND: About a third of people in the world are infected with Toxoplasma gondii. This parasite has been found in the reproductive organs and semen of males of many animal species as well as humans. The effects of toxoplasmosis on sperm count, motility and morphology were confirmed in rats. A higher prevalence of toxoplasmosis has been observed in infertile men. On the other hand, no significant effect of infection on semen parameters in men was found in one already published study. OBJECTIVES: To compare the prevalence of toxoplasmosis in men with and without semen pathology and to examine in detail the possible impact of infection on semen volume, sperm count, motility and morphology. MATERIALS AND METHODS: The pre-registered cross-sectional study included 669 men who visited the Centre for Assisted Reproduction in Prague from June 2016 until June 2018. RESULTS: The incidence of fertility problems was significantly higher in the 163 Toxoplasma-infected men (48.47%) than in the 506 Toxoplasma-free men (42.29%), τ = 0.049, P = 0.029. After correction for multiple tests, we found significantly lower sperm concentration, concentration of progressively motile sperm, and concentration of non-progressively motile sperm in Toxoplasma-positive men than in Toxoplasma-negative men using partial Kendall correlation with age controlled. In addition, toxoplasmosis correlated with sperm quality in smokers but not in non-smokers. DISCUSSION AND CONCLUSION: Our results suggest that latent toxoplasmosis affects certain semen parameters (sperm count and motility), but does not seem to affect sperm morphology and semen volume. Impairment of semen parameters may be either a side effect of the presence of Toxoplasma gondii in male reproductive organs or a product of manipulation activity of the parasite aimed to increase the efficiency of the sexual route of its transmission. Tobacco smoking also appears to exacerbate the negative impact of toxoplasmosis on semen parameters.
Keywords: Humans; toxoplazmóza; Toxoplasma gondii; reproduction; prevalence; Sperm Count; Sperm Motility; Toxoplasmosis; dospělí; fertilita; lidé; Adult; sexual transmission; motilita spermií; Male; počet spermií; Fertility; semen; Cross-Sectional Studies; mužské pohlaví; prospektivní studie; infertility; průřezové studie; Prospective Studies